An All-Solid-State Electrochemical Double-Layer Capacitor Based on a Plastic Crystal Electrolyte - Abouimrane, Ali; Belharouak, Ilias; Abu-Lebdeh, Yaser A. (Frontiers in Energy Research, 2015)
A plastic crystal, solid electrolyte was prepared by mixing tetrabutylammonium hexafluorophosphate salt, (C4H9)4NPF6, (10 molar %) with succinonitrile, SCN, (N C−CH2−CH2−C N), [SCN-10%TBA-PF6]. The resultant waxy material shows a plastic crystalline phase that extend from -36 °C up to its melting at 23 °C. It shows a high ionic conductivity reaching 4 × 10−5 S/cm in the plastic crystal phase (15 °C) and ~ 3 × 10−3 S/cm in the molten state (25 °C). These properties along with the high electrochemical stability rendered the use of this material as an electrolyte in an electrochemical double-layer capacitor (EDLC). The EDLC was assembled and its performance was tested by cyclic voltammetry, AC impedance spectroscopy and galvanostatic charge-discharge methods. Specific capacitance values in the range of 4-7 F/g. (of electrode active material) were obtained in the plastic crystal phase at 15 °C, that although compare well with those reported for some polymer electrolytes, can be still enhanced with further development of the device and its components, and only demonstrate their great potential use for capacitors as a new application.